1968
DOI: 10.1097/00006842-196801000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Intensity Control and the Cortical Evoked Response

Abstract: Cortical evoked potentials to light flashes of 4 intensities and performances on a kinesthetic figural after-effects perceptual task (KFA) were obtained from normal and nonparanoid schizophrenic subjects. In previous studies it had been shown that individual differences in perception of stimulus intensity could be inferred from KFA performance. In this study, it was hypothesized that individuals whose KFA scores indicated a tendency to reduce the perceived intensity of strong stimulation would show a comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(109 citation statements)
references
References 19 publications
(5 reference statements)
5
103
1
Order By: Relevance
“…Evidence from both older and more recent work suggests a relationship between high intensity dependence of sensory evoked potentials and such distinct personality traits as high sensation seeking, novelty seeking, extraversion, impulsivity, and psychopathy (Barrat et al 1987;Carrillo-de-la-Pena 1992;Hegerl and Juckel 1993;Hegerl et al 1989Hegerl et al , 1995aHegerl et al , 1995bJuckel et al 1995;Lukas 1987;Raine 1989;Raine and Venables 1990;Stenberg et al 1988;Zuckerman 1990;Zuckerman et al 1988). Within the augmenting/reducing concept first proposed by Buchsbaum and Silverman (1968) a high intensity dependence (augmenting) of sensory evoked activity is viewed as reflecting a central mechanism regulating neuronal sensitivity and providing the organism with an optimal level of sensory stimulation. Moreover, a relationship between high intensity dependence of sensory evoked potentials and the development of drug or alcohol abuse is also discussed in the older literature (Zuckerman 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from both older and more recent work suggests a relationship between high intensity dependence of sensory evoked potentials and such distinct personality traits as high sensation seeking, novelty seeking, extraversion, impulsivity, and psychopathy (Barrat et al 1987;Carrillo-de-la-Pena 1992;Hegerl and Juckel 1993;Hegerl et al 1989Hegerl et al , 1995aHegerl et al , 1995bJuckel et al 1995;Lukas 1987;Raine 1989;Raine and Venables 1990;Stenberg et al 1988;Zuckerman 1990;Zuckerman et al 1988). Within the augmenting/reducing concept first proposed by Buchsbaum and Silverman (1968) a high intensity dependence (augmenting) of sensory evoked activity is viewed as reflecting a central mechanism regulating neuronal sensitivity and providing the organism with an optimal level of sensory stimulation. Moreover, a relationship between high intensity dependence of sensory evoked potentials and the development of drug or alcohol abuse is also discussed in the older literature (Zuckerman 1972).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we recorded auditory evoked potentials (AEP) and used the method of dipole source analysis. An old debate exists on the dependence of the amplitude of sensory evoked potentials on stimulus intensity (Buchsbaum and Silverman 1968;review in: Carillo-dela-Pena 1992;Von Knorring and Perris 1981;Von Knorring 1982;Zuckerman et al 1974Zuckerman et al , 1988. In more recent years, extensive work suggested that a high intensity dependence is associated with a low functioning of serotonergic neurotransmission (Hegerl and Juckel 1993;Hegerl et al 1994Hegerl et al , 1996Von Knorring 1982;Von Knorring and Perris 1981).…”
mentioning
confidence: 99%
“…Interestingly, the pattern of increased P2 amplitude intensity slopes observed in the present sample of combat veterans with PTSD is strikingly similar to that reported in our previous study of female Vietnam nurse veterans with PTSD [11] (Figures 1 and 2). Additionally, the repeated measures ANOVA for P2 amplitude revealed a significant main effect for stimulus (F (3,129) = 53.0, p < 0.001) and a significant diagnosis × stimulus interaction (F (3,129) = 3.8, p = 0.04) but no main effect for diagnosis (F (1,43) = 1.3, p = 0.26). Follow-up t-test comparisons indicated that the groups did not significantly differ in P2 amplitude to the 74 dB (t (43) = 0.0 p = 0.99), 84 dB (t (43) = -1.0, p = 0.37), 94 dB (t (43) = -1.2, p = 0.24), or 104 dB (t (43) = -1.6, p = 0.11) tone.…”
Section: Electrophysiological Datamentioning
confidence: 91%
“…Because PTSD is characterized by heightened nervous system sensitivity, Paige and colleagues proposed that veterans with PTSD would show a reduction in the amplitude of the P2 component at higher tone-intensity levels, producing a shallow amplitude intensity slope [1]. Termed "reducing" by early investigators [3], this ERP response pattern of decreased intensity dependence is believed to reflect a protectively tuned sensory system that protects the organism from sensory overload via a central gating mechanism. In contrast, the opposite pattern of increasing amplitudes in response to increasing stimulus intensities (i.e., "augmenting" or increased intensity dependence) has been linked to a cortex tuned to seek out increases in stimulus intensity.…”
Section: Introductionmentioning
confidence: 99%
“…When stimuli are delivered at increasing intensity, the evoked cortical responses increase in certain individu als, but decrease in others. 98 This so called augmentingreducing response has been widely studied, mainly in the context of auditory stimuli. The intensity depend ence of AEPs (IDAP) is expressed by the amplitudestimulus intensity slope of the cortical N1-P2 wave, where N1 is the greatest negative component 60-150 ms post stimulus and P1 is the greatest positivity from 120-200 ms. Interestingly, IDAP correlates inversely with central serotonergic transmission, as evaluated indirectly by biochemical and pharmacological methods.…”
Section: Amplitude-stimulus Intensity Functionmentioning
confidence: 99%